2010
DOI: 10.1007/s11605-010-1180-4
|View full text |Cite
|
Sign up to set email alerts
|

Dose Delivery Estimated by Bremsstrahlung Imaging and Partition Model Correlated with Response Following Intra-arterial Radioembolization with 32P-Glass Microspheres for the Treatment of Hepatocellular Carcinoma

Abstract: beta-bremsstrahlung imaging following intra-arterial infusion of (32)P-glass microspheres and chemoembolization incorporates effective treatment with convenient dosimetry monitoring and manageable adverse events using a single surgical procedure. This approach is a safe and effective method for ameliorating hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
(31 reference statements)
0
8
0
1
Order By: Relevance
“…Using an intra-arterial AT-II infusion during RE may prove a way to overcome the problem of unfavorable T/N ratios, and optimize treatment-efficacy. Various studies have found an association between tumor absorbed radiation doses, tumor response and overall survival [39], [40], [41], [42]. It can, therefore, be expected that improved tumor selectivity of radioactive microsphere distribution will positively affect patient outcome after RE.…”
Section: Discussionmentioning
confidence: 99%
“…Using an intra-arterial AT-II infusion during RE may prove a way to overcome the problem of unfavorable T/N ratios, and optimize treatment-efficacy. Various studies have found an association between tumor absorbed radiation doses, tumor response and overall survival [39], [40], [41], [42]. It can, therefore, be expected that improved tumor selectivity of radioactive microsphere distribution will positively affect patient outcome after RE.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these problems, BS imaging is important in confirming the satisfactory delivery, pharmacokinetics, and potential abnormal deposition of the radiotracer [16, 2529]. Furthermore, it has been demonstrated that BS imaging is useful for the direct quantification and dosimetry of β -emitter isotopes in clinical practice [4, 30–32]. We evaluated optimized parameters for 32 P BS imaging after the RE of the hepatic tumors, and to our knowledge, this is the first clinical study to assess these factors to improve image quality.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have found an association between tumor absorbed radiation doses, tumor response and overall survival. [39,40,41,42] It can, therefore, be expected that improved tumor selectivity of radioactive microsphere distribution will positively affect patient outcome after RE.…”
Section: Author (Year)mentioning
confidence: 99%